Van der Waals epitaxy of monolayer hexagonal boron nitride on copper foil: growth, crystallography and electronic band structure. (6th May 2015) - Wood, Grace E; Marsden, Alexander J; Mudd, James J; Walker, Marc; Asensio, Maria; Avila, Jose; Chen, Kai; Bell, Gavin R; Wilson, Neil R
Abstract: We investigate the growth of hexagonal boron nitride ( h -BN) on copper foil by low pressure chemical vapour deposition (LP-CVD). At low pressure, h -BN growth proceeds through the nucleation and growth of triangular islands. Comparison between the orientation of the islands and the local crystallographic orientation of the polycrystalline copper foil reveals an epitaxial relation between the copper and h -BN, even on Cu(100) and Cu(110) regions whose symmetry is not matched to the h -BN. However, the growth rate is faster and the islands more uniformly oriented on Cu(111) grains. Angle resolved photoemission spectroscopy measurements reveal a well-defined band structure for the h -BN, consistent with a band gap of 6 eV, that is decoupled from the copper surface beneath. These results indicate that, despite a weak interaction between h -BN and copper, van der Waals epitaxy defines the long range ordering of h -BN even on polycrystalline copper foils and suggest that large area, single crystal, monolayer h -BN could be readily and cheaply produced.